(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Analysis of clinical and paraclinical characteristics and evaluation of the results of endoscopic posterior urethral valve resection surgery in children. Methods: A retrospective study was conducted on 27 cases of endoscopic posterior urethral valve resection performed at Children’s Hospital 2 between January 2015 and December 2023. Results: There were 27 cases included in the study with a median age of 4 months. Chief presenting symptoms was abnormal urination (dysuria, dribbling), observed in 44.4% of cases. The decision for primary surgery was influenced by various factors, including renal function, vesicoureteral reflux (VUR), hydronephrosis, megaureter, and the urethroscopic size relative to the patient. Primary surgery included endoscopic posterior urethral valve resection (40.7%), vesicostomy (40.7%), and endoscopic posterior urethral valve resection combined with vesicostomy (18.6%). The rate of postoperative complications was 29.6%, including residual valves and urethral stricture. Favorable outcomes were achieved in 59.3% of cases, moderate results occurred in 22.2%, and unfavorable outcomes were observed in 18.5% of instances. Conclusion: Endoscopic posterior urethral valve resection surgery is a minimally invasive technique with a high success rate and minimal complication rate in treatment of posterior urethral valve.